Pengarahan Penggunaan Media Sosial Untuk Mengembangkan Usaha Keluarga di Kelurahan Sumber Mulyorejo Binjai Timur - Rahimah, Evida; Rum Lubis, Muhammad; Rahmi Putri, Ilfi; Mauliza, Sri; Subaktiar; Kumala Dewi Ritonga, Ratih (Universitas Mataram, 2023)
This research was conducted in the city of Binjai, East Binjai District, precisely in the Sumber Mulyorejo sub-district with the aim of directing the use of social media to develop family businesses so that in the future they can increase the sales of family businesses. Housewives (IRT) can play an active role and empower all their abilities to help the family economy, one of which is through MSME activities. but there are still those who are not very active in promoting the products they produce, so they have not increased their sales turnover too much. Meanwhile, in the era of globalization, communication has used technology via the internet, one of which is through social media, even social media has been used in the business world as a fast and inexpensive sales promotion tool. MSME actors, especially family businesses in this area, need guidance on the use of social media, so they can utilize social media in promotional activities for the products they produce, so that they can help increase family business income in Sumber Mulyorejo Village, East Binjai District in the future. Family business actors responded well, a large number of them asked questions regarding the use of social media in promotional activities